Some legal issues of regulation of hunting economy in the Republic of Kazakhstan - Teleuyev Г.Б.; Bekturganov А.Е.; Yelikbay М.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The purpose of the proposed study is to improve the legal support of hunting farms in the Republic of Kazakhstan by studying their current state. The main position of the authors in the article is that the hunting industry should develop as a separate branch of the economy. The animal world permanently or temporarily inhabiting the territory of the Republic of Kazakhstan and the totality of living organisms living in conditions of natural freedom are considered an integral element of the natural environment subject to protection. Hunting is one of the oldest professions of mankind, which has existed for thousands of years and was originally the source of human existence. In the article, by analyzing the legislation of the Republic of Kazakhstan on hunting management, the existing shortcomings are identified and mechanisms for their elimination are proposed. The proposed topic is relevant and meets modern requirements. This is due to the fact that the problem of preserving biological diversity in nature is becoming an urgent problem of our society. Despite new changes in domestic legislation concerning the protection of wildlife, a comprehensive mechanism for animal protection is still considered an open question. The rational organization of the hunting economy should be used as an additional means of protecting the animal world. The authors, conducting research on the features and nature of the development of the hunting industry, proved the need to introduce a national model of the domestic hunting industry. The authors conducted a brief review of the features of the formation of the national institute of hunting economy. The ways of improving national experience are proposed, taking into account the developed hunting experience of foreign countries.